Sustainable development of community via business entity; special reference to community interest company - Murshamshul Kamariah, M.; Zuhairah Ariff, A.G.; Shahril Nizam, M.R. (2016)
Social entrepreneurship is one of the mechanisms lo overcome social or community's economic issues and to achieve sustainable development of a country. In the Southeast region, the use of business entities is mainly focus on private commercial gains. Only charitable based business entities and foundations are used to cater the economic issues of the community. In the United Kingdom , an interesting business entity known as community interest company (CIC) was introduced in 2005 to inculcate and promote social entrepreneurship among the people. CIC was introduced to address lack of vehicle to carry out non-charitable social enterprises. Generally, CICs are normal limited companies. However, different from the objectives of commercial companies, the objective of CIC is to benefit the community rather than private shareholders. In CIC, the company's assets are "locked" and could only be used for its social objectives. It is apparent that as people in all Southeast Asia's countries are mainly family-knit and